Effect of aging times of fibrous silica cadmium sulfide photoanodes for enhanced photoelectrochemical water splitting - Sawal Muhammad Hakimi; Jalil Aishah Abdul; Chowdhury Amreen; Nik Lah Nik Muhammad Izzudin (E3S Web of Conferences, 2024)
The use of photoelectrochemical (PEC) water splitting to produce hydrogen from solar sources is an alluring potential address to the world’s energy and environmental problems. Cadmium Sulfide (CdS) is a potentially visible light response photoanode of PEC water splitting, but practical use remains a significant barrier due to its low charge carrier separation efficiency. To address this disadvantage, modifications to the morphology of CdS is necessary. Herein, fibrous silica cadmium sulfide (FSCdS) photoanode for PEC water splitting was synthesized using microemulsion method reported in this study. In this study, it will be focused on the effect of aging times which is 6 hours and 8 hours on the structure of FSCdS towards the PEC water splitting. The physicochemical and electrical properties of the photoanodes were investigated using XRD, UV-Vis DRS, FTIR and EIS Nyquist Plot. FSCdS-6H had a higher photocurrent density of 22.1 mA/cm2 at 1.23 VRHE and a higher solar-to-hydrogen (STH) efficiency of 27.2% when compared to FSCdS-8H with 13.0 mA/cm2 and STH of 16.0%. This is due to the better crystallinity, higher Si-Cd-S interaction, and lower electron hole recombination rate of FSCdS-6H photoanode. Fabrication of fibrous silica-based photoanodes revealed significant insight for the creation of highperformance photoanodes for improved PEC water splitting performance.